Dinamika Lurik Klaten: Perjalanan Panjang Sehelai Kain Tenun Tradisi - Handayani, Endang Sri; Sari, Galuh pharamita (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2023)
The aim of this article is to discuss the dynamics of Lurik Klaten from the early era to its present existence. This research is descriptive-qualitative research. Lurik Klaten is a type of traditional weaving that still exists today. The existence of Lurik Klaten is the result of a long process. Starting from the traditional weaving culture using looms called gendhong, Lurik Klaten switched to ATBM (Alat Tenun Bukan Mesin; non-machinery looms) to meet the needs for clothing at the beginning of Indonesia’s independence period. The prestige of Lurik in Pedan degraded during the New Order Era with the advent of modern textile machines. This condition continued until 2006 when the government established several policies as an effort to revive it and as a community empowerment for earthquake victims